Effects of eHealth physical activity encouragement in adolescents with complex congenital heart disease: The PReVaiL randomized clinical trial. (15th October 2016) - Klausen, Susanne Hwiid; Andersen, Lars L.; Søndergaard, Lars; Jakobsen, Janus Christian; Zoffmann, Vibeke; Dideriksen, Kasper; Kruse, Anne; Mikkelsen, Ulla Ramer; Wetterslev, Jørn
Abstract: Objective: To assess benefit and harms of adding an eHealth intervention to health education and individual counseling in adolescents with congenital heart disease. Design: Randomized clinical trial. Setting: Denmark. Patients: A total of 158 adolescents aged 13–16 years with no physical activity restrictions after repaired complex congenital heart disease. Interventions: PReVaiL consisted of individually tailored eHealth encouragement physical activity for 52 weeks. All patients received 45 min of group-based health education and 15 min of individual counseling involving patients' parents. Outcomes: The primary outcome was maximal oxygen uptake (VO2 peak) at 52 weeks after randomization. The secondary outcome was physical activity. Exploratory outcomes were generic and disease-specific questionnaires. Results: In the intervention group, 58 patients (72%) completed the final test, but of those, only 46 (57%) fulfilled the compliance criteria of using the eHealth application for at least 2 consecutive weeks. In the control group, 61 patients (79%) completed both exercise tests. Adjusted for baseline values, the difference between the intervention group and the control group in mean VO2 peak at 1 year was − 0.65 ml·kg − 1 ·min − 1 (95% CI − 2.66 to 1.36). Between-group differences at 1 year in physical activity, generic health-related quality of life, and disease-specific quality of life were not statistically significant. Conclusions: Adding a tailored eHealth intervention to health education and individual counseling did not affect outcomes among adolescents with congenital heart disease. Our results do not support the use of this eHealth intervention in adolescents with complex congenital heart disease. Trial registration: Clinicaltrials.gov identifier:NCT01189981